1997
DOI: 10.1300/j009v19n03_04
|View full text |Cite
|
Sign up to set email alerts
|

A Process Evaluation of the Cultural Compatibility of Psychoeducational Family Group Treatment with Ethnic Asian Clients

Abstract: Effective ethnic-sensitive social work practice requires an understanding of the cultural compatibility between an intervention model and the client group. This study evaluated the cultural fit of psychoeducational family group treatment with ethnic Chinese and Malay families in Singapore. Process evaluation of five treatment groups determined that incompatibilities in beliefs, world views, and treatment expectations between the model and thc clients resulted in difficulties in client role behavior. Cognitive-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…In line with previous studies which advocated for taking an expert and authoritative stance in working with Asian families (19,24,26,35,36), participants (mostly carers) indicated that they would like more professional input. A unique finding in the current study is that this feedback came from the carers rather than the clients.…”
Section: Ideas For Service Developmentsupporting
confidence: 83%
See 2 more Smart Citations
“…In line with previous studies which advocated for taking an expert and authoritative stance in working with Asian families (19,24,26,35,36), participants (mostly carers) indicated that they would like more professional input. A unique finding in the current study is that this feedback came from the carers rather than the clients.…”
Section: Ideas For Service Developmentsupporting
confidence: 83%
“…It is well-documented that mutual support and learning are key therapeutic factors of MFT in working with Asian families (6,10,26). Reports from clients and carers in the current study echo findings from these Asian studies.…”
Section: Processes Of Mftsupporting
confidence: 71%
See 1 more Smart Citation
“…Attention to facilitating engagement and developing the therapeutic relationship were also significant adaptations. As Bentelspacher and his colleagues (2008) noted, although there are areas of incompatibility when applying a Western based multi‐family psychoeducational group treatment with Asian populations, support from the group facilitators through reframing and acknowledging families as a resource could help families use the group space to the families’ benefit. Apart from acknowledging the families’ effort and care to be involved in the clients’ treatment, the therapists also found it helpful to validate and normalise the families’ experience of attending the MFT.…”
Section: Discussionmentioning
confidence: 99%
“…The cultural dimension of family health revealed two primary areas of focus: family therapy (Batiste, 1990;Ben-David and Good, 1998;Bentelspacher et al, 1996;Boynton, 1987;Brown and Lamer, 1992;Daniels, 1997;Hampson, Beavers and Hulgus, 1990;Kilpatrick and Min-Jie, 1993;Long, 1986;McGill, 1992;Odell et al, 1994;Seltzer and Seltzer, 1983;Slattery, 1987) and child welfare services (Ahn, 1990;Bridgers et al, 1997;Ciliberti, 1997;Dillon, 1994;Freedman and Stark, 1993;Gray and Nybell, 1990;P.S.R.I.-Report, 1978). Further evaluation of current literature may be divided into the following categories: articles which describe various aspects of a specific cultural group (Ben- David, 1995;Dilworth-Anderson, 1992;Hall, 1978;Mayo, 1997;Segal, 1991;Weaver and White, 1997), articles which provide cross-cultural comparisons often focusing on a particular social problem such as child abuse (Brownlee, 1978;McGee, 1997;Soydan, 1995), and articles which explore evaluations of programs identifying appropriateness for various cultures (Oyemade, 1985;Schnur et al 1995;Washington, 1985).…”
Section: Cultural Dimension Of Family Healthmentioning
confidence: 99%